Pendampingan Penyusunan Bahan Ajar Berbasis Digital bagi Guru di Sekolah Indonesia Kuala Lumpur Malaysia - Han Tantri Hardini; Rochmawati Rochmawati; Agung Listiadi; Joni Susilowibowo (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
In the digital technology era, schools are expected to be able to implement teaching materials through technology-based media to deliver learning content effectively. Therefore, the PKM team aims to assist teachers at Sekolah Indonesia Kuala Lumpur (SIKL) in developing technology-based teaching materials. The results of the training and mentoring sessions show that teachers are highly interested in the training on digital-based teaching materials. The teachers stated that the material presented during the training was clearly explained and easy to understand, particularly in the context of implementing online learning. The time required for the training activities was very efficient and effective, and the teachers found it to be much-needed. A total of 100% of the teachers agreed to use digital teaching materials after receiving the training. The conclusion of this community service is that the assistance provided aligns with the teachers' needs, as technology-based teaching materials are well-suited for both online and offline learning, enabling students to learn anytime and anywhere. The teachers' response to the teaching materials training was very positive. This program has had a significant impact on enhancing the teachers' understanding of developing digital teaching materials, which can contribute to improving the quality of education at Sekolah Indonesia Kuala Lumpur.